The Effect of Social Media Use, Exercise Habits, and Social Support on Mental Health of College Students in Indonesia - Hartatik Hartatik; Septin Maisharah K; Dina Destari; Inayatul Mutmainnah (West Science Social and Humanities Studies, 2023)
Through a quantitative analysis employing structural equation modeling (SEM-PLS), this study examines the complex links between social media use, exercise habits, social support, and mental health among 210 college students in Indonesia. To investigate how these variables interact, descriptive statistics, measurement model evaluation, and structural model analysis were performed. The results highlighted the influence of online interactions on psychological well-being by showing a strong positive correlation between social media use and mental health. Although there was a positive correlation between exercise habits and mental health, it was not statistically significant, suggesting that more research is necessary. Social support has been shown to be a strong indicator of mental health, emphasizing the importance of interpersonal relationships. Validity and reliability of the model were indicated by its fit indices, and path analysis highlighted the importance of these components in influencing mental health outcomes. The results have consequences for programs and laws meant to promote mental wellness among college students.